Carcinoma neuroendocrino de células pequeñas de la amígdala: Notas Clínicas - Arsénio Barbosa; Miguel Relvas; Clara Borges; MArgarida Sá-Fernandes (Sociedade Galega de Medicina Interna, 2000)
Primary small neuroendocrine carcinoma (SNEC) of the tonsil it's a rarity. We present the case of a 64 year-old Caucasian male patient referred to our hospital due to a neck mass. A fixed non-tender rock hard supraclavicular right mass and ipsilateral cervical lymphadenopathy was palpable. Biopsy was performed and showed poor differentiated neoplasm with features of SNEC. A fludeoxyglucose positron emission tomography (FDG-PET) scan showed intense uptake in the right tonsil. The patient underwent right tonsillectomy and immunochemistry was positive for characteristic features of small cell neuroendocrine carcinoma. Right tonsil SNEC was diagnosed and the patient was proposed to chemotherapy.